Poziomy kontroli wypłacalności zakładów ubezpieczeń zgodnie z zaleceniami IAIS - Kurek, Robert (Solvency Control Levels of Insurance Companies Following IAIS Recommendations, 2006)
The article presents assumptions elaborated by IAIS with regard to solvency control levels. The problem was referred to in principles and recommendations elaborated by IAIS, which arc the determinants of national regulations within IAIS member countries. It refers to both the European Union countries and other countries in the world, whose separate legal systems may, in a totally different way than in EU, determine supervisory activities related to insurance companies solvency. Solvency control levels have been given special place in the study, since they were distinguished by the European Commission as basic instruments for determining supervisory competencies in the system of solvency assessment based on total risk, i.e. so called Solvency II project.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 82-93